2005
DOI: 10.1128/cdli.12.12.1437-1441.2005
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Interferon Is Dispensable for Neopterin Production In Vivo

Abstract: Previous studies have indicated that neopterin is synthesized in vitro by human monocyte-derived macrophages and dendritic cells upon stimulation with gamma interferon (IFN-␥). Neopterin production under specific conditions in vitro has also been obtained upon stimulation with IFN-␣ and/or IFN-␤. However, it is unknown if any IFN-␥-independent neopterin synthesis is possible in vivo. In the present study we investigated the serum neopterin concentrations in patients affected by the syndrome of Mendelian suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…However the reason for the observed discrepancies in CSF CXCL12 levels between ADEM and the other two groups of encephalitis (EVE and anti-NMDAR E) is not clear [ 50 ]. We did not see any correlation between CSF neopterin and IFN-γ or α (data not shown) in contrast to the previous hypothesis that IFN-γ and IFN-α induced neopterin synthesis [ 51 , 52 ] suggesting the possibility of alternate immune mechanisms of neopterin production [ 53 ].…”
Section: Discussioncontrasting
confidence: 99%
“…However the reason for the observed discrepancies in CSF CXCL12 levels between ADEM and the other two groups of encephalitis (EVE and anti-NMDAR E) is not clear [ 50 ]. We did not see any correlation between CSF neopterin and IFN-γ or α (data not shown) in contrast to the previous hypothesis that IFN-γ and IFN-α induced neopterin synthesis [ 51 , 52 ] suggesting the possibility of alternate immune mechanisms of neopterin production [ 53 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, in this study despite a significant decrease in serum neopterin and IFN-γ cytokine in patients undergoing allogeneic blood transfusion, no correlation was observed between the two phenomena. This investigation was supported by Sghiri et al (2005), who demonstrated that IFN-γ is not the only stimulus in vivo needed for the synthesis of neopterin in patients with impairment of the IFN-γ pathway. Therefore, rather than the depressed secretion of IFN-γ cytokine, we speculate that allogeneic blood transfusion directly and/or by other cytokines down-regulates monocytes/macrophage function to exert their inhibitory and regulatory properties on neopterin production.…”
Section: ) Cd3mentioning
confidence: 72%
“…Plasma and urine neopterin levels increase in HIV/AIDS 38, cytomegalovirus infection, hepatitis A and B virus 39, and in other conditions which mediate the Th1 response 38. Neopterin is induced by IFN α/β and was recently shown to be produced in vivo independently of IFN-γ 40, indicating that other factors may be able to stimulate neopterin. Biopterin is biotransformed from neopterin, and similarly increased during the IFN-γ stimulated immune response.…”
Section: Resultsmentioning
confidence: 99%